Responsibility-sensitive welfare weights for health - Matthew Robson; Owen O'Donnell; Tom Van Ourti (Tinbergen Institute, 2024)
We estimate responsibility-sensitive welfare weights for health that facilitate inequalityand inequity-sensitive policy evaluation. In a UK general population sample, 569 online experiment participants distribute constrained resources to determine the health of hypothetical individuals distinguished by randomly generated resource productivity as well as sex, income and smoking (41,460 observations). We elicit beliefs about responsibility for income and smoking, and use their associations with the allocations to estimate responsibility-sensitive weights that reflect inequality aversion and health prioritisation by the non-health characteristics. There is slight, moderate and substantial prioritisation of females, the poor and non-smokers, respectively. Inequality aversion lowers weights on females and non-smokers, who are health-advantaged, and raises the weight on the poor, who are health-disadvantaged. As beliefs about responsibility for income and smoking strengthen, weights on the poor decrease and weights on non-smokers significantly increase.
Keywords: C90; D30; D63; I14; I38; 330; Experiment; Social Preferences; Inequality Aversion; Equity